2014
DOI: 10.1152/ajprenal.00521.2014
|View full text |Cite
|
Sign up to set email alerts
|

Combination of ACE inhibitor with nicorandil provides further protection in chronic kidney disease

Abstract: An inhibition in the renin-angiotensin system (RAS) is one of the most widely used therapies to treat chronic kidney disease. However, its effect is occasionally not sufficient and additional treatments may be required. Recently, we reported that nicorandil exhibited renoprotective effects in a mouse model of diabetic nephropathy. Here we examined if nicorandil can provide an additive protection on enalapril in chronic kidney disease. Single treatment with either enalapril or nicorandil significantly ameliorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…This process may subsequently induce Ca 2+ -dependent-apoptosis (Efanova et al 1998). Several studies have shown that the opening of the K ATP channel is renoprotective (Shiraishi et al 2014; Assad et al 2009; Zhang et al 2013). So, SUs might have detrimental effects on kidney, which is a concern in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…This process may subsequently induce Ca 2+ -dependent-apoptosis (Efanova et al 1998). Several studies have shown that the opening of the K ATP channel is renoprotective (Shiraishi et al 2014; Assad et al 2009; Zhang et al 2013). So, SUs might have detrimental effects on kidney, which is a concern in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Sirt3 has also been demonstrated to protect against podocyte injury as the target of the membrane G protein-coupled receptor 5 (TGR5) in kidney injuries caused by obesity and diabetes mellitus [50]. In addition, Shiraishi et al [51] provided direct evidence that nicorandil may synergize with enalapril to alleviate chronic kidney injuries via regulation Sirt3. Our studies have highlighted the role of Sirt6 in podocytes, which has pleiotropic protective actions including anti-inflammatory and antiapoptotic effects, maintenance of the actin cytoskeleton, and promotion of autophagy [9].…”
Section: Nad + -Dependent Deacetylases On the Regulation Of Podocyte mentioning
confidence: 99%
“…In addition, Tamura et al (2012) demonstrated the renoprotective effects of nicorandil on a rat remnant kidney model of chronic kidney disease. Moreover, Shiraishi et al (2014) demonstrated that nicorandil might synergize with renoprotective effects of enalapril in chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, nicorandil (K ATP channel opener) pretreatment caused upregulation of nrf2 in aortic tissues obtained from rats treated with high adenine diet at the level of mRNA suggesting improvement of oxidative stress in aortic tissues might reduce the aortic calcifications. The antioxidant action of nicorandil was demonstrated in a rat model of remnant kidney disease (Tamura et al 2012;Shiraishi et al 2014), rat model of renal I/R injury (Ozturk et al 2017) and brain injury after cardiac arrest in pigs (Zhu et al 2018). Endothelial dysfunctions in chronic kidney disease was demonstrated in high adenine rat model and occurred in the form of imbalance between the vasodilators (serum nitric oxide) and vasoconstrictors (serum endothelin) (Peng et al 2013;Ali et al 2015).…”
Section: Control Control Adeninementioning
confidence: 99%